Enhancing the design of data-related privacy controls for smart home devices - Chhetri, Chola; Motti, Vivian Genaro (Information and computer security, 2023)
Purpose Past research shows that users of smart home devices (SHDs) have privacy concerns. These concerns have been validated from technical research that shows SHDs introduce a lot of privacy risks. However, there is limited research in addressing these concerns and risks. This paper aims to bridge this gap by informing the design of data-related privacy controls for SHDs. Design/methodology/approach In this paper, the authors follow a user-centered design approach to design data-related privacy controls from design requirements backed by literature. The authors test the design for usability and perceived information control using psychometrically validated scales. For this purpose, two variations of the prototype (MyCam1 with a listing of data-related privacy controls and MyCam2 with three privacy presets) were created and tested them in a between-subjects experimental setting. Study participants (n = 207) were recruited via Mechanical Turk and asked to use the prototype app. An online survey was distributed to the participants to measure some usability and privacy-related constructs. Findings Findings show that the presented prototype designs were usable and met the privacy control needs of users. The prototype design with privacy presets (MyCam2) was found to be significantly more usable than the list of privacy controls (MyCam1). Originality The findings of this paper are original and build on the paper presented at the International Symposium on Human Aspects of Information Security and Assurance (HAISA 2022). This paper contributes improved and usable designs of privacy controls for smart home applications.